Flame-retardant heat-shrinkable insulating sleeve material, flame-retardant heat-shrinkable insulating sleeve and preparation method thereof

By grafting a combination of material A and flame retardant B, the problems of complex processes and poor flame retardant capabilities of traditional heat shrinkage materials are achieved. The natural cross-linking process is adopted to reduce costs and process complexity, and excellent flame retardant performance is achieved while ensuring the shrinkage performance of the material.

CN116199965BActive Publication Date: 2025-03-04CGN HIGH-TECH NUCLEAR MATERIALS (HEBEI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310131531.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-03-04
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

Traditional heat shrinkable materials use chemical crosslinking or irradiation crosslinking, which has harsh process conditions or expensive equipment, which is not conducive to large-scale production, and has poor flame retardant capabilities, which is prone to fire.

Method used

The combination of silane grafted material A and flame retardant B is used to realize the preparation of flame retardant heat shrink insulated sleeve material through natural cross-linking. The process is simple, low-cost, easy to produce on a large scale, and excellent flame retardant performance while ensuring the shrinkage performance of the material.

Benefits of technology

It realizes self-crosslinking of materials, reduces production costs and process complexity, and also has excellent flame retardant properties, avoids fire hazards, and has broad application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004084076800000091
    Figure BDA0004084076800000091
Patent Text Reader

Abstract

The present invention provides a flame retardant heat shrinkable insulation sleeve material, a flame retardant heat shrinkable insulation sleeve and a preparation method thereof. The flame retardant heat shrinkable insulation sleeve material provided in the present application comprises a silane grafted A material and a flame retardant B material in a mass ratio of (3-5):25. In terms of mass fractions, the material of the silane grafted A material comprises 85-95 parts of a first base resin, 1-5 parts of a silane coupling agent, 0.1-1 parts of an initiator and 0.5-1 parts of an optional first antioxidant; the material of the flame retardant B material comprises 100 parts of a second base resin, 35-45 parts of a flame retardant, 0.1-0.5 parts of a catalyst and 0.5-2 parts of an optional second antioxidant. The flame retardant heat shrinkable insulation sleeve material provided in the present application can not only achieve natural crosslinking by placement, has a simple process and low cost, but also has excellent flame retardant properties while ensuring the shrinkage performance of the material, thereby avoiding fire hazards.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant polymer materials, and in particular to a flame retardant heat shrinkable insulating sleeve material, a flame retardant heat shrinkable insulating sleeve and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of domestic manufacturing, energy, construction engineering and other fields, the demand for electrical equipment has continued to increase, which has been accompanied by the increasing demand for polymer insulation materials. Electrical equipment usually operates under high temperature and complex electromagnetic environment conditions, while traditional polymer materials usually have poor heat resistance and flame retardancy. When electrical equipment is overloaded, high temperature, arc, etc., it is very easy to melt and burn, causing irreversible economic losses. The use of cross-linking technology to form a three-dimensional network structure of polymer materials can greatly improve their resistance to high temperature and complex environments. The main cross-linking methods are chemical cross-linking and radiation cross-linking. Among them, chemical cross-linking has strict requirements on the material processing temperature, usually requiring the material processing temperature not to exceed 135°C. Radiation cross-linking technology requires the use of expensive radiation processing equipment and the construction of special radiation plants, and there is a certain degree of danger in the processing process.

[0003] In addition, since traditional heat shrink materials are mostly made of cross-linked polyethylene, in order to make the material have certain heat shrinkage properties, little or no flame retardant fillers are usually added, so it basically has no flame retardant ability. When overload occurs, the conductor material often becomes red and hot, and the high temperature causes the outer layer of insulating material to decompose or even burn, causing irreversible fire hazards.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The main purpose of the present invention is to provide a flame retardant heat shrinkable insulating sleeve material, a flame retardant heat shrinkable insulating sleeve and a preparation method thereof, so as to solve the problem that traditional heat shrinkable materials use chemical crosslinking or radiation crosslinking, have harsh process conditions or expensive equipment, are not conducive to large-scale production, have poor flame retardancy, and are prone to fire.

[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a flame retardant heat shrinkable insulating sleeve material is provided, and the insulating heat shrinkable insulating sleeve material comprises a silane grafted A material and a flame retardant B material, and the mass ratio of the two is (3-5):25; in terms of mass parts, the material of the silane grafted A material comprises 85-95 parts of a first base resin, 1-5 parts of a silane coupling agent, 0.1-1 parts of an initiator and 0.5-1 parts of an optional first antioxidant; the material of the flame retardant B material comprises 100 parts of a second base resin, 35-45 parts of a flame retardant, 0.1-0.5 parts of a catalyst and 0.5-2 parts of an optional second antioxidant.

[0007] Furthermore, in the self-crosslinking heat shrinkable tube material, the mass ratio of the silane grafted A material to the flame retardant B material is (3.5-4.5):25, preferably 4:25.

[0008] Further, the first matrix resin includes at least one of LDPE resin, LLDPE resin, ethylene-vinyl acetate copolymer, EPDM rubber, ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer or ethylene-ethyl acrylate copolymer.

[0009] Furthermore, the silane coupling agent is an ethyl silane coupling agent, and the vinyl silane coupling agent includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, 3-methacryloxypropyl trimethoxy silane or vinyl trimethoxyethoxy silane.

[0010] Furthermore, the initiator is dicumyl peroxide.

[0011] Further, the first antioxidant is at least one of antioxidant 1010 , antioxidant DLTP, antioxidant 168 , antioxidant 1035 or antioxidant 300 .

[0012] Further, the second matrix resin includes at least one of LDPE resin, LLDPE resin, ethylene-vinyl acetate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer, and ethylene-ethyl acrylate copolymer.

[0013] Furthermore, the second matrix resin also includes a compatibilizer, and preferably the compatibilizer is at least one of ethylene-maleic anhydride graft copolymer and ethylene hexene-maleic anhydride graft copolymer.

[0014] Furthermore, the flame retardant includes a compound IFR flame retardant and a layered silicate, and the mass ratio of the two is (30-35): (5-10), the compound IFR flame retardant includes at least two of piperazine pyrophosphate, nano zinc oxide, melamine cyanurate, melamine polyphosphate, and ammonium polyphosphate, and more preferably the compound IFR flame retardant is a mixture of piperazine pyrophosphate, nano zinc oxide and melamine cyanurate, and the mass ratio of the three is (10-20): 1:3; the layered silicate includes at least one of modified nano montmorillonite, modified kaolin attapulgite clay, organic bentonite or sepiolite.

[0015] Furthermore, the catalyst is dibutyltin dilaurate.

[0016] Further, the second antioxidant includes at least one of antioxidant 1010 , antioxidant DLTP, antioxidant 168 , antioxidant 1035 or antioxidant 300 .

[0017] Further, in parts by mass, the first matrix resin includes 50 to 60 parts of LDPE resin, 15 to 25 parts of ethylene-vinyl acetate copolymer, and 10 to 20 parts of ethylene-methyl methacrylate copolymer; or, the first matrix resin includes 35 to 45 parts of LDPE resin, 5 to 15 parts of EPDM rubber, 15 to 25 parts of ethylene-vinyl acetate copolymer, and 15 to 25 parts of ethylene methyl acrylate copolymer.

[0018] Further, the second matrix resin includes 30-40 parts of LDPE resin, 30-40 parts of ethylene-vinyl acetate copolymer, 15-25 parts of ethylene-ethyl acrylate copolymer, and 5-15 parts of ethylene-maleic anhydride graft copolymer, calculated by mass; or, the second matrix resin includes 25-35 parts of LDPE resin, 35-45 parts of ethylene-vinyl acetate copolymer, 10-20 parts of ethylene-ethyl acrylate copolymer, and 10-20 parts of ethylene hexene-maleic anhydride graft copolymer.

[0019] Furthermore, the preparation method of the silane grafted A material comprises the following steps: mixing the materials of the silane grafted A material including the first base resin, the silane coupling agent, the initiator and the optional first antioxidant, and then extruding and granulating them to obtain the silane grafted A material.

[0020] Furthermore, the preparation method of the flame retardant B material comprises the following steps: mixing the flame retardant B material including the second base resin, the flame retardant, the catalyst and the optional second antioxidant, and then extruding and granulating the mixture to obtain the flame retardant B material.

[0021] According to a second aspect of the present application, a flame retardant heat shrinkable insulating sleeve is also provided. The flame retardant heat shrinkable insulating sleeve is made of a self-crosslinking heat shrinkable sleeve material.

[0022] According to the third aspect of the present application, a method for preparing a flame retardant heat shrinkable insulating sleeve is also provided, the preparation method comprising the following steps: mixing a silane grafted material A and a flame retardant material B, extruding and coating the mixture on the outer surface of a conductor, and cooling the mixture to obtain a flame retardant heat shrinkable insulating sleeve.

[0023] By applying the technical solution of the present application, the present application uses silane-grafted material A and flame-retardant material B to cooperate with each other as a flame-retardant heat-shrinkable insulating sleeve material. Not only can it achieve natural cross-linking by placement, but it also has a simple process, low cost, and is easy to achieve large-scale production. It also has excellent flame-retardant properties while ensuring the shrinkage performance of the material, avoiding fire hazards, and has broad application prospects. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0025] As analyzed in the background technology of this application, traditional heat shrinkable materials are prepared by chemical crosslinking or radiation crosslinking, which has harsh process conditions or expensive equipment, is not conducive to large-scale production, and has poor flame retardancy and is prone to fire. In order to solve this problem, this application provides a flame retardant heat shrinkable insulation sleeve material, a flame retardant heat shrinkable insulation sleeve and a preparation method thereof.

[0026] In a first typical embodiment of the present application, a flame retardant heat shrinkable insulating sleeve material is provided, which includes a silane grafted A material and a flame retardant B material, and the mass ratio of the two is (3-5):25; in terms of mass fractions, the material of the silane grafted A material includes 85-95 parts of a first base resin, 1-5 parts of a silane coupling agent, 0.1-1 parts of an initiator and 0.5-1 parts of an optional first antioxidant; the material of the flame retardant B material includes 100 parts of a second base resin, 35-45 parts of a flame retardant, 0.1-0.5 parts of a catalyst and 0.5-2 parts of an optional second antioxidant.

[0027] By applying the technical solution of the present application, the present application uses silane-grafted material A and flame-retardant material B to cooperate with each other as a flame-retardant heat-shrinkable insulating sleeve material. Not only can it achieve natural cross-linking by placement, but it also has a simple process, low cost, and is easy to achieve large-scale production. It also has excellent flame-retardant properties while ensuring the shrinkage performance of the material, avoiding fire hazards, and has broad application prospects.

[0028] Typically but not restrictively, in the flame-retardant heat shrinkable tubing material provided in the present application, the mass ratio of the silane grafted A material and the flame-retardant B material is, for example, 3:25, 3.5:25, 4:25, 4.5:25, 5:25 or a range consisting of any two numerical values; in the silane grafted A material, the mass fraction of the first matrix resin is, for example, 85 parts, 88 parts, 90 parts, 92 parts, 95 parts or a range consisting of any two numerical values; the mass fraction of the silane coupling agent is, for example, 1 part, 2 parts, 3 parts, 5 parts or a range consisting of any two numerical values, the mass fraction of the initiator is, for example, 0.1 part, 0.2 part, 0.5 part, 0.8 part, 1 part or a range consisting of any two numerical values; the mass fraction of the first antioxidant is, for example, 0.5 part, 0.6 part, 0.8 part, 1 part or a range consisting of any two numerical values.

[0029] Among the above-mentioned flame-retardant heat-shrinkable insulating sleeve materials, the mass ratio of silane grafted material A and flame-retardant material B is preferably (3.5-4.5):25. The flame-retardant heat-shrinkable insulating sleeve material has excellent flame retardant properties and heat shrinkage properties, especially when the mass ratio of silane grafted material A and flame retardant material B is 4:25, the flame retardant heat-shrinkable sleeve material has more excellent flame retardant properties and heat shrinkage properties.

[0030] In the above-mentioned silane grafted material A, the first matrix resin includes but is not limited to LDPE resin (low density polyethylene), LLDPE resin (linear low density polyethylene), ethylene-vinyl acetate copolymer, EPDM rubber, ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer or ethylene-ethyl acrylate copolymer, any one or a mixture of two or more thereof.

[0031] In order to further improve the heat shrinkage performance of the flame-retardant heat shrinkable tubing material, the melt flow rate (190°C @ 2.16kg) of the LDPE resin is preferably 1.5 to 2.0 g / 10min; the melt flow rate (190°C @ 2.16kg) of the LLDPE is 1.5 to 20.0 g / 10min; the melt flow rate (190°C @ 2.16kg) of the ethylene-vinyl acetate copolymer is 2.0 to 6.0 g / 10min; the Mooney viscosity range ML100°C (1+4) of the EPDM rubber is 45 to 95, the melt flow rate (190°C @ 2.16kg) of the ethylene-methyl methacrylate copolymer is 0.1 to 20.0 g / 10min; the melt flow rate (190°C @ 2.16kg) of the ethylene-propylene-ethyl acrylate copolymer is 1.5 to 20.0 g / 10min.

[0032] The specific source of the above LDPE resin is not limited, such as Daqing Petrochemical 2426H or Yanshan Petrochemical LD-100AC; the specific source of the above LLDPE resin is not limited, such as Sabic HP2023JN, 222WT or Maoming Petrochemical 7042; the specific source of ethylene-vinyl acetate copolymer is not limited, such as ExxonMobil UL00328 or Lianhong Chemical UL00428, BASF-Yangzi Chemical V5110J; EPDM rubber There is no limitation on the specific source, such as 477P of Dow Chemical or 7001 of ExxonMobil; there is no limitation on the specific source of ethylene-methyl methacrylate copolymer, such as WH102, WD106, WH206 of Sumitomo Chemical; there is no limitation on the specific source of ethylene-methyl acrylate copolymer, such as 8525, 1820 of Dow Chemical; there is no limitation on the specific source of ethylene-ethyl acrylate copolymer, such as 3002 of Dow Chemical or 4503 of Arkema.

[0033] The above-mentioned silane coupling agent is preferably a vinyl silane coupling agent, so as to facilitate the cross-linking reaction between the silane coupling agent and the first matrix resin to obtain the silane-modified A material. The specific type of the vinyl silane coupling agent is not limited, and any vinyl silane coupling agent commonly used in the art can be used, including but not limited to any one of vinyl trimethoxy silane, vinyl triethoxy silane, 3-methacryloxy trimethoxy silane or vinyl trimethoxyethoxy silane, or a mixture of two or more thereof.

[0034] The specific type of the above-mentioned initiator is not particularly limited, and any initiator commonly used in the art can be used, including but not limited to dicumyl peroxide.

[0035] The specific type of the first antioxidant is not specifically limited, and any commonly used antioxidant in the art can be used, including but not limited to any one of antioxidant 1010, antioxidant DLTP, antioxidant 168, antioxidant 1035 or antioxidant 300, or a mixture of two or more thereof.

[0036] In order to further improve the mechanical properties and flame retardant properties of the flame retardant heat shrinkable insulating sleeve material, the first matrix resin preferably includes 50 to 60 parts of LDPE, 15 to 25 parts of ethylene-vinyl acetate copolymer, and 10 to 20 parts of ethylene-methyl methacrylate copolymer, by weight; or, the first matrix resin includes 35 to 45 parts of LDPE resin, 5 to 15 parts of EPDM rubber, 15 to 25 parts of ethylene-vinyl acetate copolymer, and 15 to 25 parts of ethylene methyl acrylate copolymer.

[0037] In some embodiments of the present application, the preparation method of silane grafted A material includes the following steps: mixing the materials of silane grafted A material including a first base resin, a silane coupling agent, an initiator and an optional first oxidant, and then extruding and granulating to obtain silane grafted A material.

[0038] In order to further improve the mixing efficiency, the mixing is preferably carried out in a high-speed mixer, and the mixing time is preferably 15 to 20 minutes.

[0039] The extrusion granulation is preferably carried out in a twin-screw extruder to further improve the extrusion granulation efficiency.

[0040] In the above-mentioned extrusion granulation process, the raw materials of the silane-grafted A material undergo a silane grafting reaction in the extrusion stage, and the process includes: the initiator decomposes under heat to produce highly active free radicals, the free radicals capture the hydrogen atoms on the polyethylene segment in the first matrix resin, and the polyethylene segment forms a macromolecular free radical, and then the macromolecular free radical reacts with the vinyl group of silane to form the silane-grafted A material.

[0041] In the flame retardant B material, the second matrix resin includes but is not limited to any one of LDPE resin, LLDPE resin, ethylene-vinyl acetate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer, and ethylene-ethyl acrylate copolymer, or a mixture of two or more thereof.

[0042] The above-mentioned LDPE resin, LLDPE resin, ethylene-vinyl acetate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer, and ethylene-ethyl acrylate copolymer are as described in the first resin above, and will not be repeated here.

[0043] In order to further improve the dispersibility of the flame retardant in the flame retardant B material, the second base resin preferably also includes a compatibilizer, and the compatibilizer includes any one of ethylene-maleic anhydride graft copolymer and ethylene hexene-maleic anhydride graft copolymer or a mixture of two or more thereof.

[0044] In order to further improve the flame retardant properties of the flame retardant heat shrinkable insulation sleeve material, the flame retardant preferably includes a compounded IFR flame retardant and a layered silicate, and the mass ratio of the two is (30-35): (5-10) to achieve excellent flame retardant properties at a relatively low addition amount; wherein the compounded IFR flame retardant includes at least two of piperazine pyrophosphate, nano zinc oxide, melamine cyanurate (MCA), melamine polyphosphate, and ammonium polyphosphate; the layered silicate is a layered silicate commonly used in the art, including but not limited to any one or a mixture of two or more of modified nano montmorillonite, modified kaolin attapulgite clay, organic bentonite or sepiolite. In particular, when the compounded IFR flame retardant is a mixture of piperazine pyrophosphate, nano zinc oxide and melamine cyanurate, and the mass ratio of the three is 10-20:1:3, the flame retardant effect of the flame retardant heat shrinkable insulation sleeve material is more excellent.

[0045] Typically but not limiting, in the compound IFR flame retardant, the mass ratio of piperazine pyrophosphate, nano zinc oxide and melamine cyanurate is 10:1:3, 12:1:3, 15:1:3, 18:1:3, 20:1:3 or a range consisting of any two values.

[0046] The specific type of the above catalyst is not limited, and includes but is not limited to dibutyltin dilaurate.

[0047] The specific type of the second oxidant is the same as the first oxidant and will not be described in detail here.

[0048] In order to further improve the flame retardant properties of the flame retardant heat shrinkable insulating sleeve material and the dispersion uniformity of the flame retardant B material, the second matrix resin preferably includes 30 to 40 parts of LDPE resin, 30 to 40 parts of ethylene-vinyl acetate copolymer, 15 to 25 parts of ethylene-ethyl acrylate copolymer, and 5 to 15 parts of ethylene maleic anhydride graft copolymer, by weight; or, the second matrix resin includes 25 to 35 parts of LDPE resin, 35 to 45 parts of ethylene-vinyl acetate copolymer, 10 to 20 parts of ethylene-ethyl acrylate copolymer, and 10 to 20 parts of ethylene hexene-maleic anhydride graft copolymer.

[0049] In some embodiments of the present application, the method for preparing flame retardant B material comprises the following steps: mixing the flame retardant B material including a second base resin, a flame retardant, a catalyst and an optional second oxidant, and then extruding and granulating to obtain flame retardant B material.

[0050] The above mixing is preferably carried out in a high-speed mixer to further improve the mixing uniformity and shorten the mixing time. The mixing time is preferably 10 to 20 minutes.

[0051] In a second typical embodiment of the present application, a flame retardant heat shrinkable insulating sleeve is further provided. The flame retardant heat shrinkable insulating sleeve is made of any flame retardant heat shrinkable insulating sleeve material provided in the above-mentioned first typical embodiment.

[0052] The flame-retardant heat-shrinkable insulating sleeve provided in the present application is formed by the cooperation of silane-grafted material A and flame-retardant material B through silicone cross-linking. It not only has excellent mechanical properties and flame-retardant properties, but also has a simple preparation process, low cost, and is easy to achieve large-scale production.

[0053] In the third typical embodiment of the present application, a method for preparing the above-mentioned flame retardant heat shrinkable sleeve is also provided, and the preparation method includes the following steps: mixing the silane grafted A material and the flame retardant B material, extruding and coating the mixture on the outer surface of the conductor, and cooling the mixture to obtain a flame retardant heat shrinkable insulating sleeve.

[0054] The preparation method of the flame-retardant heat shrinkable tubing provided in the present application has a simple process, is easy to operate, is easy to realize large-scale production, reduces production costs, and improves production efficiency.

[0055] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0056] Example 1

[0057] This embodiment provides a self-flame retardant heat shrinkable insulating sleeve material, which is composed of a silane grafted A material and a flame retardant B material, and the mass ratio of the silane grafted A material to the flame retardant B material is 4:25.

[0058] The materials of silane grafted material A include the following components by mass: 55 parts of low-density polyethylene resin, 20 parts of ethylene-vinyl acetate copolymer resin, 15 parts of ethylene-methyl methacrylate copolymer resin, 5 parts of vinyl trimethoxy silane, 0.6 parts of 1010 antioxidant, 0.4 parts of 168 antioxidant, and 1 part of diisopropylbenzene peroxide; wherein the melt index of the low-density polyethylene resin is 1.8 g / 10 min (190°C @ 2.16 kg); the ethylene-vinyl acetate copolymer The melt index of the resin is 6.0 g / 10 min (190°C @ 2.16 kg); the melt index of the ethylene-methyl methacrylate copolymer resin is 0.2 g / 10 min (190°C @ 2.16 kg). The silane grafted A material is prepared according to the following steps: the components of the above-mentioned silane grafted A material are placed in a high-speed mixer and mixed for 15 minutes to obtain a mixed material; the mixed material is transferred to a twin-screw extruder for extrusion granulation and drying to obtain a silane grafted A material.

[0059] The flame retardant B material includes the following components by mass: 35 parts of ethylene-vinyl acetate resin copolymer, 20 parts of ethylene-ethyl acrylate copolymer, 35 parts of low-density polyethylene resin, 10 parts of ethylene-maleic anhydride graft copolymer, 30 parts of compound IFR flame retardant (piperazine pyrophosphate: nano zinc oxide: MCA 15:1:3), 5 parts of organic layered silicate flame retardant, 0.5 parts of 1010 antioxidant, 0.5 parts of DLTP antioxidant, 0.5 parts of UV-326 ultraviolet absorber, 0.5 parts of UV-944 anti-ultraviolet agent, and 0.5 parts of dibutyltin dilaurate; wherein the melt index of ethylene-vinyl acetate resin copolymer is 3.0g / 10min (190℃@2.16kg); the melt index of ethylene-ethyl acrylate copolymer resin is 5.0g / 10min (190℃@2.16kg); the melt index of low-density polyethylene resin is 1g / 10min (190℃@2.16kg); the organic layered silicate is nano-montmorillonite.

[0060] The flame retardant B material is prepared according to the following steps: placing the components of the flame retardant B material in a high-speed mixer and mixing for 15 minutes to obtain a mixed material; transferring the mixed material to a twin-screw extruder for extrusion granulation and drying to obtain the flame retardant B material.

[0061] Example 2

[0062] The difference between this embodiment and embodiment 1 is that the materials of the silane grafted material A include the following components in parts by mass: 40 parts of low-density polyethylene resin, 10 parts of ethylene-vinyl acetate copolymer resin, 20 parts of ethylene-methyl acrylate copolymer, 5 parts of vinyl trimethoxy silane, 0.6 parts of 1010 antioxidant, 0.4 parts of DLTP antioxidant, and 1 part of diisopropylbenzene peroxide; wherein the melt index of the low-density polyethylene resin is 1.8 g / 10 min (190°C @ 2.16 kg); the melt index of the ethylene-vinyl acetate copolymer resin is 4.0 g / 10 min (190°C @ 2.16 kg); and the melt index of the ethylene-methyl acrylate copolymer resin is 0.2 g / 10 min (190°C @ 2.16 kg).

[0063] The materials of flame retardant B material include the following components by mass: 40 parts of ethylene-vinyl acetate copolymer, 15 parts of ethylene-ethyl acrylate copolymer resin, 30 parts of low-density polyethylene resin, and 15 parts of ethylene hexene-maleic anhydride graft copolymer. Compound IFR flame retardant 35 parts, organic layered silicate flame retardant 10 parts, 1010 antioxidant 1 part, DLTP antioxidant 0.5 parts, dibutyltin dilaurate 0.5 parts; among them, the melt index of ethylene-vinyl acetate resin copolymer is 3.0g / 10min((190℃@2.16kg); the melt index of ethylene-ethyl acrylate copolymer resin is 3.0g10 / min (or purchased from xx manufacturer, model xx); the melt index of low-density polyethylene resin is 1.8g / 10min; the organic layered silicate is sepiolite.

[0064] Example 3

[0065] The difference between this embodiment and embodiment 1 is that the compound IFR flame retardant is composed of piperazine pyrophosphate and nano zinc oxide, and the mass ratio of the two is 15:4.

[0066] Example 4

[0067] The difference between this embodiment and embodiment 1 is that the compound IFR flame retardant consists of piperazine pyrophosphate and MCA, and the mass ratio of the two is 15:4.

[0068] Example 5

[0069] The difference between this embodiment and embodiment 1 is that the compound IFR flame retardant is composed of nano zinc oxide and MCA, and the mass ratio of the two is 1:3.

[0070] Example 6

[0071] The difference between this embodiment and embodiment 1 is that piperazine pyrophosphate is used to replace the flame retardant of the compound IFR.

[0072] Example 7

[0073] The difference between this embodiment and embodiment 1 is that the amount of organic layered silicate used is 2 parts, and the amount of the flame retardant of the compounded IFR is 33 parts.

[0074] Example 8

[0075] The difference between this embodiment and embodiment 1 is that the amount of organic layered silicate used is 20 parts, and the amount of the compounded IFR flame retardant is 15 parts.

[0076] Example 9

[0077] The difference between this embodiment and embodiment 1 is that no organic layered silicate is added, and the flame retardant of the compounded IFR is 35 parts.

[0078] Example 10

[0079] The difference between this embodiment and embodiment 1 is that the amount of organic layered silicate used is 35 parts, and no flame retardant of compound IFR is added.

[0080] Embodiment 11

[0081] The difference between this embodiment and embodiment 1 is that the mass ratio of silane material A to flame retardant material B is 3:25.

[0082] Example 12

[0083] The difference between this embodiment and embodiment 1 is that the mass ratio of silane material A to flame retardant material B is 5:25.

[0084] Comparative Example 1

[0085] The difference between this comparative example and Example 1 is that the mass ratio of silane material A to flame retardant material B is 2:25.

[0086] Comparative Example 2

[0087] The difference between this comparative example and Example 1 is that the mass ratio of silane material A to flame retardant material B is 8:25.

[0088] Comparative Example 3

[0089] The difference between this comparative example and Example 1 is that the amount of the compounded IFR flame retardant is 20 parts and the amount of the organic layered silicate flame retardant is 2 parts.

[0090] Test Example 1

[0091] The flame retardant heat shrinkable insulating sleeve materials provided in the above-mentioned embodiment and comparative example are mixed evenly, extruded and coated on the outer surface of the conductor by a single screw extruder, and cooled to obtain a flame retardant heat shrinkable insulating sleeve, and the thickness of the flame retardant heat shrinkable insulating sleeve is xxmm.

[0092] The tensile strength, elongation at break, flame retardancy and volume conductivity of the flame retardant heat shrinkable insulating sleeve were measured respectively, and the results are shown in Table 1 below.

[0093] Table 1

[0094]

[0095] By analyzing the test results of the above examples and comparative examples, it can be found that when the mass ratio of silane grafted A material and flame retardant B material is (3-5):25, and a high-efficiency compounded IFR flame retardant is used with an organic layered silicate, the material has good mechanical properties and excellent flame retardant properties. When the components or ratios of silane grafted A material and flame retardant B material are changed, it is impossible to simultaneously take into account excellent mechanical properties and flame retardant properties.

[0096] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: through the material design of silane grafted A material and flame retardant B material, the flame retardant heat shrinkable insulation sleeve material has self-crosslinking ability. By using a high-efficiency IFR compound flame retardant with an organic layered silicate flame retardant as a flame retardant system, the flame retardant heat shrinkable insulation sleeve material still has excellent flame retardant effect at a low flame retardant addition amount, avoiding fire hazards and having broad application prospects.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A flame retardant heat shrinkable insulating sleeve material, characterized in that: The flame retardant heat shrinkable insulating sleeve material comprises a silane grafted A material and a flame retardant B material, and the mass ratio of the two is (3-5):25; By weight, the materials of the silane-grafted A material include 85-95 parts of a first base resin, 1-5 parts of a silane coupling agent, 0.1-1 parts of an initiator, and 0.5-1 parts of an optional first antioxidant; the materials of the flame-retardant B material include 100 parts of a second base resin, 35-45 parts of a flame retardant, 0.1-0.5 parts of a catalyst, and 0.5-2 parts of an optional second antioxidant; The flame retardant comprises a composite IFR flame retardant and a layered silicate, and the mass ratio of the two is (30-35): (5-10); the composite IFR flame retardant is a mixture of piperazine pyrophosphate, nano zinc oxide and melamine cyanurate, and the mass ratio of the three is (10-20): 1: 3; the layered silicate comprises at least one of modified nano montmorillonite, modified kaolin attapulgite clay, organic bentonite or sepiolite; In parts by mass, the first matrix resin includes 50-60 parts of LDPE resin, 15-25 parts of ethylene-vinyl acetate copolymer, and 10-20 parts of ethylene-methyl methacrylate copolymer; or, the first matrix resin includes 35-45 parts of LDPE resin, 5-15 parts of EPDM rubber, 15-25 parts of ethylene-vinyl acetate copolymer, and 15-25 parts of ethylene methyl acrylate copolymer; In parts by mass, the second matrix resin includes 30 to 40 parts of LDPE resin, 30 to 40 parts of ethylene-vinyl acetate copolymer, 15 to 25 parts of ethylene-ethyl acrylate copolymer, and 5 to 15 parts of ethylene-maleic anhydride graft copolymer; or, the second matrix resin includes 25 to 35 parts of LDPE resin, 35 to 45 parts of ethylene-vinyl acetate copolymer, 10 to 20 parts of ethylene-ethyl acrylate copolymer, and 10 to 20 parts of ethylene hexene-maleic anhydride graft copolymer.

2. The flame retardant heat shrinkable insulating sleeve material according to claim 1, characterized in that: In the flame-retardant heat-shrinkable insulating sleeve material, the mass ratio of the silane-grafted A material to the flame-retardant B material is (3.5-4.5):

25.

3. The flame retardant heat shrinkable insulating sleeve material according to claim 1, characterized in that: In the flame-retardant heat-shrinkable insulating sleeve material, the mass ratio of the silane-grafted A material to the flame-retardant B material is 4:

25.

4. The flame retardant heat shrinkable insulating sleeve material according to claim 1, characterized in that: The silane coupling agent is a vinyl silane coupling agent, and the vinyl silane coupling agent includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, 3-methacryloxypropyl trimethoxy silane or vinyl trimethoxyethoxy silane; And / or, the initiator is dicumyl peroxide; And / or, the first antioxidant is at least one of antioxidant 1010 , antioxidant DLTP, antioxidant 168 , antioxidant 1035 or antioxidant 300 .

5. The flame retardant heat shrinkable insulating sleeve material according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate; And / or, the second antioxidant includes at least one of antioxidant 1010 , antioxidant DLTP, antioxidant 168 , antioxidant 1035 or antioxidant 300 .

6. The flame retardant heat shrinkable insulating sleeve material according to any one of claims 1 to 5, characterized in that: The preparation method of the silane grafted material A comprises the following steps: mixing the materials of the silane grafted material A including the first base resin, the silane coupling agent, the initiator and the optional first antioxidant, and then extruding and granulating them to obtain the silane grafted material A.

7. The flame retardant heat shrinkable insulating sleeve material according to any one of claims 1 to 5, characterized in that: The method for preparing the flame retardant B material comprises the following steps: mixing the flame retardant B material including the second base resin, the flame retardant, the catalyst and the optional second antioxidant, and then extruding and granulating the mixture to obtain the flame retardant B material.

8. A flame retardant heat shrinkable insulating sleeve, characterized in that: The flame retardant heat shrinkable insulating sleeve is made of the flame retardant heat shrinkable insulating sleeve material according to any one of claims 1 to 5.

9. The method for preparing the flame-retardant heat-shrinkable insulating sleeve according to claim 8, characterized in that: The preparation method comprises the following steps: mixing the silane grafted A material and the flame retardant B material, extruding and coating the mixture on the outer surface of the conductor, and cooling the mixture to obtain the flame retardant heat shrinkable insulating sleeve.

Citation Information

Patent Citations

  • Two-step process silane crosslinking low-smoke halogen-free flame-retarding polyolefin cable material and manufacturing method of same

    CN106589564A

  • Anti-yellowing halogen-free flame-retardant polyolefin composition and preparation method thereof

    CN113388193A